Sonographic Characteristics of Apocrine Nodular Hidradenoma of the Skin. (7th September 2017) - Wortsman, Ximena; Reyes, Carlos; Ferreira‐Wortsman, Camila; Uribe, Alberto; Misad, Carlos; Gonzalez, Sergio
Abstract : Nodular hidradenomas are benign sweat gland–derived tumors that can produce clinical and dermatoscopic misdiagnoses. Histologically, these tumors can be classified into eccrine and apocrine subtypes. We present the sonographic characteristics of 6 cases of apocrine nodular hidradenomas, which, to our knowledge, is so far the largest series reported. A detailed sonographic analysis included layers, body location, shape, diameters, echostructure patterns, and vascularity. Two sonographic signs not previously reported in these or other common dermatologic lesions were detected: "snow falling" and "fluid‐fluid level." The sonographic characteristics of apocrine nodular hidradenomas can support their earlier and more precise diagnosis.